ChemInform Abstract: Reductive Coupling Reaction of Aldehydes Using Indium(III) Triflate as the Catalyst. Issue 48 (2nd December 2014) - Mineno, Tomoko; Tsukagoshi, Rie; Iijima, Tsubasa; Watanabe, Kazuki; Miyashita, Hiroyuki; Yoshimitsu, Hitoshi
Abstract A facile protocol for the conversion of aldehydes into the corresponding symmetrical ethers is developed.